L’industrie dans le paysage des villes et des territoires. Illustrations en Lorraine - Jean-Marie Simon (Bulletin de l’Association de Géographes Français)
In France at the beginning of the 20th century, industrial dynamism is disrupting territories organized around agriculture and the classical city. The land needs, for industrial establishments accompanying infrastructures and housing of a large workforce and low income, require the appropriation of land most often agricultural. The action of industrialists through the "Musée social" leads to the first French town planning law passed in 1919: the Cornudet law. The law shows its relevance during the reconstruction following the First World War, but it is modified in 1925 and its effectiveness is greatly reduced. The municipalities must now finance operations in less than fifteen years: any ambitious project or land reserves is then virtually excluded. This “victory” of the landowners hampers the action of communities that must acquire land at market prices and no longer agricultural land, so they intervene on a case-by-case basis, according to requests or opportunities. The first landscapes marked by industrial development appeared at the beginning of the 20th century and they illustrate the city hoped for by industrialists and for which they are involved. The latter are the result of local projects developed in an emergency to solve an employment crisis; finally, the third appear in current attempts at reindustrialization. These landscapes, the daily living environment of workers and consumers, are evolving, and knowledge of their origin and the scale of the major construction communities (municipalities-metropolitan areas-regions-Europe) will have to accompany programming and planning actions.